AUTOAGRESSIVE BEHAVIORS AND BODY IMAGE IN WOMEN WITH EATING DISORDERS - MIODUCHOWSKA-ZIENKIEWICZ, AGNIESZKA (Studia Psychologica: Theoria et praxis, 2015)
The purpose of this article is to present the phenomena of eating disorders, body image and autoaggressive behaviour and to attempt to present the relationship between these variables in women with eating disorders. The study group (clinical) in the project consisted of 25 women diagnosed with anorexia or bulimia, while the control group contained30 healthy women. The research made use of the following methods: The Body Self Questionnaire (J-C Scale) by Beata Mirucka and the Inventory of the Psychological Aggression Syndrome (IPSA-II) by Zbigniew B. Gaś. The analysis of the results showed that women with anorexia and bulimia, had higher autoaggressive tendencies compared to healthy women. In addition, in the study group the disturbed body image significantly correlated with the increased autoaggressive behavior. The obtained results are discussed in the context of the existing research findings and theories.